The evaluation of the research on the biofuels: a scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the literature on the biofuels published during the last three decades, based on the databases of Science Citation Index Expanded (SCIE) and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this study reveal that the literature on the biofuels has grown exponentially during this period reaching 6,770 papers in total with paralleling enormous changes in the research landscape. Papers mostly have been journal articles, reviews, and proceedings, predominantly in English. USA, China, and Germany have been the three most prolific countries. The "University of Illinois" has been the most prolific institution. The most prolific authors have been "Demirbas A" and "Minter SD". "Biomass & Bioenergy" has been the most prolific journal whilst, "Energy Fuels" has been the most prolific subject area. The total number of citations is 79,304, giving a ratio for the "Average Citations per Item" as 11.71 and "H-index" as 101. Ragauskas et al. has had the highest impact on the literature. Both the research output and the citations have thrived spectacularly after 2005. The results of this first ever such study of its kind, show that the scientometric analysis has a great potential to gain valuable insights into the evolution of the high-profile research on the biofuels, complementing other research techniques.
Keywords: Biofuels; Research evaluation; Scientometrics; Web of Knowledge